Pola Komunikasi Orang Tua Dalam Pembentukan Karakter Anak Usia Dini - Adinda Shofia Mutmainna (Indonesian Journal of Elementary and Childhood Education, 2024)
This study aims to understand the role of parental communication patterns in shaping children's character. Using a descriptive qualitative approach, the research involved five pairs of parents and five children as the main subjects. Data were collected through observation and in-depth interviews and analyzed thematically through reduction, presentation, and conclusion-drawing stages. The findings reveal that effective communication, such as open interaction, attentive dialogue, and providing examples of positive behavior, plays a crucial role in shaping children's character, including empathy, responsibility, and openness. Conversely, minimal communication patterns, such as neglect or lack of quality time, tend to trigger negative behaviors in children, such as disobedience and social isolation. This study highlights the vital role of parents in establishing healthy and consistent communication patterns as the foundation for shaping children's personality. Moreover, the findings offer practical insights to help families enhance the quality of their daily interactions. Thus, this research not only emphasizes the importance of positive communication patterns but also encourages further exploration of external factors, such as social environments or technology, that may influence family communication dynamics.